Removal of AS(III) and AS (V) from contaminated water sources by sorption onto novel pei-attached poly(hipe) beads", paper presented at international conference on ?role of analytical chemistry in nuclear technology? - Ingavle, Ganesh C.; Tayal, Rajeev; Shaikh, Wasif Abdul Lateef; Chaudhari, Sanjeev; Chavan, Nayaku; Rajan, Chelanattukizhakkemadath Raman; Ponrathnam, Surendra (Role of Analytical Chemistry in Nuclear Technology, 2007)

Role of interfacial tension of solvating diluents and hydrophilic-hydrophobic cross-linkers in hyper-cross-linked solid supports - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (Industrial & Engineering Chemistry Research, 2015)
The properties of a hyper-cross-linked solid support are the outcome Of the interfacial tension created by solvating/nonsolvating diluents, the hydrophilicity/hydrophobicity of the cross-linkers, and their concentrations. Interestingly, a More hydrophobic diluent and cross-linker as well as a higher concentration of cross-linker-containing copolymer revealed an increase In surface area. A high surface area and low cross-link density (CLD) polymer illustrated higher epoxy content. Importantly, maximum surface area (533 m(2)/g) Was obtained at high CLD; inversely, epoxy,content (1.83 mmol/g) was higher at low CLD polymer. Notably, greater rigidity of cross-linker and its higher concentration increased T-max and T-g; contrarily, greater flexibility of cross-linker and its concentration attenuated T-max and T-g. Thermal study demonstrated the thermostability (300 degrees C) and polymer safe temperature (220 degrees C). Indeed, a lower solubility parameter difference between polymer and swelling solvent produces a higher polymer-solvent interaction parameter, resulting in increased polymer swelling. Polymers with high surface area and low CLD demonstrated greater swelling behavior.

Role of aliphatic hydrocarbon content in non-solvating porogens toward porosity of cross-linked microbeads - Mane, Sachin; Badiger, Manohar V.; Rajan, C. R.; Ponrathnam, Surendra; Chavan, Nayaku (Polymer, 2016)
Megaporous spherical acrylate copolymer beads were synthesized by suspension polymerization using non-solvating porogens. Non-solvating porogens with higher aliphatic hydrocarbon content generated megaporous morphology with lower surface area. Surface area increased and inversely megaporosity was decreased with decrease in the aliphatic hydrocarbon content of porogen. Megaporosity (5.47 mu m) and pore volume of 5.52 cm(3)/g was obtained with n-decanol. Thermal property of copolymer is a function of type (rigidity/flexibility/elemental composition) and concentration (cross-link density) of monomer and cross-linker. Copolymer containing rigid cross-linker (divinylbenzene) had better thermal stability over copolymer with flexible cross-linker (ethylene dimethacrylate). Further, higher concentration of rigid cross-linker or lower concentration of flexible cross-linker enhanced the thermal stability. Porous polymers are potentially recognized as a solid support for solid-phase synthesis. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Cross-linked microbeads; Interfacial tension; Megaporosity; Non-solvating porogens; Thermal properties